Height in Turner syndrome: Does Growth Hormone Therapy Have Impact? - Roche, Edna; Gadelsayed, Montasser (My University, 2014)
Short stature is a cardinal feature of Turner syndrome. We examined height outcome and its relation to growth hormone therapy in Irish girls with Turner syndrome. In those with Turner syndrome (TS), the adult stature is an average 20 cm shorter than the general population1. By 15 years of age, the average height of an untreated girl with TS is equivalent to that of only a 9.5-year-old girl in the general population2. We therefore set out to describe height outcome in Irish girls with TS. The impact of growth hormone (GH) therapy on height was also examined. Height measurement was taken according to the standard guidelines. Mean height standard deviation scores (SDS) was calculated. Fisher’s Exact test was used to compare groups and the association between the height and age at GH initiation or duration of GH therapy and was assessed using regression analysis.
PUBLISHED
Keywords: Turner syndrome